Kemiskinan dan agihan pendapatan di kawasan transmigrasi dan bukan transmigrasi: Kajian kes di Kampar, Riau - Zargustin, Dedi (2015)
Indonesia is one of the developing and middle income countries with a GDP growth rate of 6.2 percent in 2012. However, Indonesia faced a significant poverty problem especially in the rural areas and poverty is highly associated with rural sector. Therefore, the government had emphasized on the rural sector development through population resettlement policies under the transmigration program since the Second Five Year Development Plan (REPELITA: 1974-1979). This is the largest resettlement program in the world. Unfortunately, in implementing the poverty eradication policy, the government presumed that the problem and characteristics of the rural society are relatively similar. Indeed, most previous researches revealed that they are different. Poverty and income distribution are influenced by several factors such as the socioeconomic, culture and social institution backgrounds of the population. Thus, this study intends to analyse factors affecting the poverty and income distribution inequality within transmigration and non-transmigration areas located in Kabupaten Kampar. This study used a descriptive and quantitative analysis based on a stratified random sampling, involving face to face interviews with 752 respondents. The Multiple Linear Regression model were applied to analyze the factors affecting distribution of income, the Logistic Regressions model with maximum likelihood approach were used to analyze the factors affecting poverty, while the Chi Square test used to analyse the determinants of poverty. The determining factors tested for poverty and income distribution were the size of land, the use of technology, level of education, status of health, accessibility to institutions and off-farm income. Overall, the inequality of income distribution is much greater in a non-transmigration area compared to transmigration areas. However, the gap is significantly reduced when an off-farm income were added to the main employment (farm produce) of the head of households’ income. Almost all variables tested had significantly negative relation with distribution of income, while different income determinant contributed differently toward total yield per hectare in both areas. Overall, the revenue per hectare was higher in the transmigration area, leading towards higher average income levels and lower poverty rate for the transmigration as compared to non-transmigration areas. In conclusion, the development policy for poverty eradication and income distribution should be focused on increasing the capacity of human resources, increasing business opportunities, improving physical property ownership, enabling access to institutions and increasing the use of technology, especially within specified location